2014
DOI: 10.1007/s00132-013-2188-8
|View full text |Cite
|
Sign up to set email alerts
|

Moderne unikondyläre Kniearthroplastik

Abstract: Zusammenfassung Hintergrund Die unikondyläre Kniearthroplastik (UKA) ist bei fortgeschrittener medialer oder lateraler Gonarthrose eine etablierte Therapieoption. Ziel der Arbeit Die Eckpfeiler einer erfolgreichen UKA – sorgfältige Patientenselektion, präoperative Planung und präzise Operationstechnik – werden in dieser Übersichtsarbeit behandelt. Stellenwert Im Unterschied zur Knietot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…While the long-term successful results of UKA are known in the literature, the importance of patient, surgeon, and implant related factors has been reported (20)(21)(22)(23)(24). In this study, we found similar good clinical, functional, and radiological results, and low revision rates in both designs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…While the long-term successful results of UKA are known in the literature, the importance of patient, surgeon, and implant related factors has been reported (20)(21)(22)(23)(24). In this study, we found similar good clinical, functional, and radiological results, and low revision rates in both designs.…”
Section: Discussionsupporting
confidence: 68%
“…Even if there is no mechanical or radiological problem in patients with intense pain after UKA, revision surgery (TKA) can be decided quickly (19). UKA tends to be performed on younger and more active patients than TKA, which is why functional comparison of UKA and TKA may be misleading (24). For these reasons, we compared UKA patients among themselves, as MB-UKA versus FB-UKA.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al[14] conducted a retrospective study including 229 knees and found that younger patients had better results than older patients and body mass index (BMI) had no direct association with failure rate. It is justified to broaden classic UKA indications owing to the study performed by von Knoch et al[15]. The main reasons for failure in UKA includes the defects on prosthesis design, a lack of experience in surgical techniques, the progression of arthritis, and inadequate patient selection[16].…”
Section: Introductionmentioning
confidence: 99%